Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/v13040559
|View full text |Cite
|
Sign up to set email alerts
|

Focus on HPV Infection and the Molecular Mechanisms of Oral Carcinogenesis

Abstract: This study is focused on the epidemiological characteristics and biomolecular mechanisms that lead to the development of precancerous and cancerous conditions of oral lesions related to Human Papilloma Virus (HPV) infections. Current evidence from the literature demonstrates the role of HPV in potentially malignant oral disorders. Therefore, the underlying biomolecular processes can give arise, or contribute to, benign lesions as well as to oral carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 60 publications
(89 reference statements)
0
32
0
Order By: Relevance
“…Instead, in North America and Europe, high risk human papillomavirus (HPV) infections are responsible for a growing percentage of oropharyngeal cancers among young people; for other infectious agents, this link is still debated (e.g., it has been reported that different species belonging to the Candida spp. (mostly Candida albicans) that produce endogenous nitrosamines from dietary nitrites are present in the oral cavity, especially in saliva) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, in North America and Europe, high risk human papillomavirus (HPV) infections are responsible for a growing percentage of oropharyngeal cancers among young people; for other infectious agents, this link is still debated (e.g., it has been reported that different species belonging to the Candida spp. (mostly Candida albicans) that produce endogenous nitrosamines from dietary nitrites are present in the oral cavity, especially in saliva) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Although HPV-associated cancer occurs in various body parts, including the oral cavity [ 53 ], anus [ 54 ], vagina [ 55 ], vulva [ 56 ], and penis [ 57 ], we focus only on two major cancer types, cancers of the uterine cervix [ 58 ] and head and neck [ 59 ].…”
Section: Diversity Of Tumor Virusesmentioning
confidence: 99%
“…HPVs are members of the Papillomaviridae (PV) family, presenting a circular, with supercoiled and double-stranded DNA, and some are considered as oncogenic promoters [64][65][66]. The virus has a hexahedral symmetry capsid (consisting of pentameric capsomeres) and has two structural proteins, L1 and L2 [67,68].…”
Section: The Role Of Human Papillomavirus (Hpv)mentioning
confidence: 99%